Lecturer’s Strategies in Teaching Speaking at Sintuwu Maroso University - Vivin Krismawanti Modjanggo; Ismianti Y Akay (Sintuwu Maroso Journal of English Teaching, 2021)
The objective of this research are to find out the strategies used by the lecturer in teaching Speaking subject and to find out students’ responses towards the strategies that are used by the lecturer. This research uses a descriptive qualitative approach. This research uses observation, interview, and questionnaire to collect the data. The subject  of this research are lecturer who teach Survival Speaking subject and 21 students in the second semester of  English Education Study Program in 2020/2021 academic year. The result of this research  obtains that there are three strategies that are used by the lecturer in teaching Survial Speaking subject, namely ; Brainstorming, Small-Group Discussion, and Demonstration. The students responses towards strategies are used by the lecturer can be seen from the result of the questionnaire, the students responses are ; students likes survival speaking subject, interest in the strategies used by the lecturer in speaking subject, can pay attention when the lecturer provide survival speaking subject, strategies used by the lecturer make students feel easy to speak English well, motivated to speak in front of the class because the strategies used by the lecturer, make students understand new words that are hear in the survival speaking subject, more understand the material given by the lecturer, also feel happy to give opinions and questions to lecturer during survival speaking subject, and like the strategies used by the lecturer when giving assignments and evaluation in the survival speaking subject.